Environmental friendly device: modeling of carbon nanotube with optimum chirality - Farhana, Soheli; Alam, A. H. M. Zahirul (INSI Publications, 2013)
An optimum chirality of carbon nanotube (CNT) is modeled and analyzed in this paper. CNT is a tubular form which is made from a graphene sheet. Thus only graphene can be contributed through its' electronic properties to setup an optimum CNT. Therefore, First we describe the geometrical structure calculation and then analyzed the graphene electronic structure and thus this graphene surface forms a nanotube. Theses electronic properties are designed from tight binding (TB) model for graphene. Furthermore, geometrical calculation shows that misalignment and pyramidzation angle with chirality (25,0) which is semiconducting zigzag for SWCNT and MWCNT. Finally the minimum value of CNT bandgap of 0.4401eV shows that the optimum chirality is (25,0) for the modeling of carbon nanotube.